Modernization of the cable car in order to take into account the length of the metal cord at the stage of its final production - S. F. Brezgun; A. S. Negru (Литьë и металлургия)
To achieve accuracy and stability in measuring the length of the metal cord at the stage of its manufacture, it is necessary to modernize the existing rope-twisting equipment. The upgrade introduced a new algorithm for rope-twisting equipment, changed the length accounting system of the steel cord, used the latest equipment and technology. A contactless electric power transmission system and a wireless data transmission system based on an infrared channel have been introduced.The use of the latest technologies and our own innovations allowed us to obtain a completely new type of rope-twisting machine that can produce metal cord according to the requirements of the consumer’s specification.